Books Still Worth Reading - Virginia Association of Teachers of English; McLeod, Alan M.; Virginia Association of Teachers of English ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
The 10 major articles in this special journal issue deal with literary works designated by individual educators as "still worth reading." The works discussed are (1) "Madeline" by L. Bemelmans; (2) "The Assistant" by B. Malamud; (3) "The Pitfalls for Readers of Fiction" by H. Sample, the first of the pamphlet publications by the National Council of Teachers of English; (4) "The Old Man and the Sea" by E. Hemingway; (5) "Emma" by Jane Austen; (6) "Lord Jim" by J. Conrad; (7) "The Gold of Troy: The Story of Heinrick Schleimann and the Buried Cities of Ancient Greece" by R. Payne; (8) The "Scarlet Letter" by N. Hawthorne; (9) "Charlotte's Web" by E. B. White; and (10) "The Rime of the Ancient Mariner" by S. Coleridge. Additional articles discuss literature as period study, black literary classics, choosing books for young adults, literature that teaches about reading, and the reading preferences of adults and adolescents. (FL)
ERIC Note: The Virginia Association of Teachers of English and Language Arts is an affiliate of the National Council of Teachers of English.
Virginia English Bulletin, v33 n1 Spr 1983.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescent Literature; Adults; Black Literature; Books; Childrens Literature; Elementary Secondary Education; English Instruction; Literature; Literature Appreciation; Poetry; Reading Instruction; Reading Interests; Teaching Methods; Collected Works, Serials; Guides, Classroom -- Teacher